Body growth of North Atlantic right whales (Eubalaena glacialis) revisited. Issue 2 (27th October 2020) - Fortune, Sarah M. E.; Moore, Michael J.; Perryman, Wayne L.; Trites, Andrew W.
Abstract: Knowing size‐at‐age is important for determining food requirements and making inferences about the nutritional status of individuals and their populations. Accurate growth curves are also needed to quantify drug dosages to treat wounded or entangled animals. However, body sizes are often based on small numbers of measured animals that must be improved as new data become available. We updated an existing body growth model for North Atlantic right whales (NARWs) using new data from dead animals and from older individuals. Our models indicate that NARWs attain mean lengths and weights of 4.3 m and 1.0 mt at birth, and 13.1 m and 31.7 mt when sexually mature. Calves more than double their length and attain nearly three‐quarters of their asymptotic adult size during their first year of life. Overall, our length estimates agreed well with previous estimates, but our mass‐at‐age values were considerably higher. These differences revealed that necropsy data used alone in allometric models underestimate mass due possibly to several of the stranded animals in the database having been chronically entangled and in poor body condition. Augmenting the database with healthier individuals, such as harvested North Pacific right whales, yielded mass predictions that reflect both healthy and unhealthy individuals.